Malaria burden and pre-hospital medication among subjects with malaria in Maiduguri, Northeast Nigeria - Sulayman T. Balogun (Heliyon, 2019)
The study re-visited malaria burden and pre-hospital medication among malarious subjects in Maiduguri, Northeast Nigeria. A total of 1,657 febrile subjects were screened for malaria by microscopy at two health institutions. Giemsa-stained blood smears were examined for parasitaemia and gametocytaemia; and parasite density (PD), gametocyte density (GD) and gametocyte sex ratio (GSR) were determined. The mean age of the 1,657 subjects was 27.5 ± 12.2 years and 7.8% (130/1,657) of the subjects aged <5 years. Sex distribution showed 47.0% (778/1,657) males and 53.0% (879/1657) females. Parasitaemia was recorded in 22.6% (375/1,657) with geometric mean PD of 8,925 (320–275,000) parasites/μl blood. The prevalence of parasitaemia was highest among subjects <5 years (χ2 = 401.1; df = 5; p < 0.0001) and in August and September (χ2 = 406.9; df = 11; p < 0.0001). Prevalence of gametocytaemia was 12.8% (48/375) with geometric mean GD of 109 (8–464) gametocytes/μl blood. The prevalence was higher in dry (16.5%, 29/176) than wet (9.5%, 19/199) months (χ2 = 4.0; df = 1; p = 0.045). The weighted mean GSR was 0.4 ± 0.1 with highest value in March (0.7 ± 0.2). Pre-hospital medication was recorded in 74.1% (278/375) of the subjects with parasitaemia. Analgesics (51.7%; 194/375) accounted for the highest proportion of drug consumed while 9.3% (35/375) of the subjects took antimalarial drugs. Malaria persisted in Maiduguri especially among subjects <5 years during wet months and pre-hospital medication is a common practice. These findings could serve as guide for policy decision that could contribute to effective treatment and control of malaria in the region.